2018
DOI: 10.3390/su10061914
|View full text |Cite
|
Sign up to set email alerts
|

Academic Relational Civility as a Key Resource for Sustaining Well-Being

Abstract: In the 21st century, which has been characterized by complexity, instability, and continuous change, the well-being of individuals is threatened. The health and well-being of individuals are recognized as one of the 17 sustainable development goals of the United Nations. From a primary prevention perspective, physical and psychological health can be augmented through the early identification and promotion of key psychological resources that sustain well-being across one's lifetime. With that goal in mind, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 62 publications
(101 reference statements)
4
13
0
Order By: Relevance
“…Future research could also continue to study in depth the relationships between the new integrated construct of HELP and personality traits to see if these results will be confirmed or will emerge specificities in relation to different categories and contexts. Notwithstanding the highlighted limitations, the results of this work offers new opportunities for future research and interventions from a primary prevention perspective (Hage et al, 2007; Kenny and Hage, 2009; Di Fabio and Kenny, 2016b; Di Fabio, 2017a) for entrepreneurs, workers, and healthy organizations in the 21st century (Tetrick and Peiró, 2012; Di Fabio and Palazzeschi, 2012; Di Fabio et al, 2016; Di Fabio and Kenny, 2016a; Di Fabio and Gori, 2016b; Dempsey and Kauffman, 2017; Di Fabio and Peiró, 2018). HELP can be considered as preventive individual resources to successfully face with the challenges of the current continuous changing labor market.…”
Section: Discussionmentioning
confidence: 99%
“…Future research could also continue to study in depth the relationships between the new integrated construct of HELP and personality traits to see if these results will be confirmed or will emerge specificities in relation to different categories and contexts. Notwithstanding the highlighted limitations, the results of this work offers new opportunities for future research and interventions from a primary prevention perspective (Hage et al, 2007; Kenny and Hage, 2009; Di Fabio and Kenny, 2016b; Di Fabio, 2017a) for entrepreneurs, workers, and healthy organizations in the 21st century (Tetrick and Peiró, 2012; Di Fabio and Palazzeschi, 2012; Di Fabio et al, 2016; Di Fabio and Kenny, 2016a; Di Fabio and Gori, 2016b; Dempsey and Kauffman, 2017; Di Fabio and Peiró, 2018). HELP can be considered as preventive individual resources to successfully face with the challenges of the current continuous changing labor market.…”
Section: Discussionmentioning
confidence: 99%
“…The social context of adjustment is of paramount importance, and previous sustainability research has found social ties, such as academic relational civility, to have profound impacts on wellbeing [24]. In the case of international students, acquaintances with host nationals has facilitated psychological adjustment [5].…”
Section: Multidimensional Predictors Of Sociocultural Adaptationmentioning
confidence: 99%
“…Regarding the strengths that can be invigorated for the relationships with others, we have resources that can be enhanced in terms of workplace relational civility [27] and its specific application in an academic context in terms of academic relational civility [14,36]. Workplace Relational Civility [37] is defined as a relational style "characterized [sic] by respect and concern for oneself and others, interpersonal sensitivity, personal education, and kindness toward others.…”
Section: Confucianismmentioning
confidence: 99%
“…Relational decency at work, in terms of relationships based on decency and characterized by respect for the self and others, being able to express beliefs and opinions freely, assertiveness, being tactful; Relational culture at work, in terms of courtesy, kindness, politeness; Relational readiness at work, in terms of speed in understanding the feelings of others and exhibiting proactive sensibility, ability to understand the emotions of others, delicacy, empathy, and compassion. Academic relational civility presents the same dimensions but with respect to the organizational specific academic context [14,36]. Workplace relational civility implies a scale with a mirror modality of evaluation (me with others, part A, and others with me, part B) allowing an in-depth evaluation of interpersonal interactions considering one's own contribution and the contribution of others in relationships.…”
Section: Confucianismmentioning
confidence: 99%